Variability in clinical laboratory practice in testing for disorders of platelet function - Moffat, Karen A.; Ledford-Kraemer, Marlies R.; Nichols, William L.; Hayward, Catherine P. M. (Thrombosis and Haemostasis, 2005)
Disorders of platelet function are important causes of abnormal bleeding that require laboratory tests for diagnosis. Currently there are limited guidelines on how to perform clinical testing for these disorders. The goal of our study was to obtain information on how disorders of platelet function are currently evaluated in clinical laboratories. Two patterns-of-practice surveys were distributed to laboratories of the North American Specialized Coagulation Laboratory Association (NASCOLA). The information collected was analyzed to determine practices and common problems. Forty-seven NASCOLA laboratories participated and 54% completed both surveys. The majority of the laboratories that responded performed more than 50 aggregation tests per year, mainly using platelet rich plasma based methodologies. A minority performed testing for platelet secretion and dense granule abnormalities. While platelet aggregation results were reviewed in various ways, laboratories most commonly issued a combined report containing quantitative values (% aggregation and/or slope) and a qualitative interpretation. Although laboratories used similar agonists for aggregation testing, the final agonist concentrations varied widely. Several approaches were also used to obtain reference intervals. Comments offered by the participants indicated that performing, and interpreting platelet function tests were challenging for many clinical laboratories. Although common practices have evolved, there is considerable variability in the diagnostic test procedures used by clinical laboratories to evaluate disorders of platelet function. These patterns-of-practice surveys illustrate a need for guidelines and recommendations for clinical laboratories performing tests of platelet function.
Keywords: Platelet disorders; platelet function testing; platelet secretion